2022
DOI: 10.3389/fnut.2022.883264
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the Dietary Magnesium Intake and Magnesium Depletion Score With Osteoporosis Among American Adults: Data From the National Health and Nutrition Examination Survey

Abstract: ObjectivesThe study aimed to explore the associations between dietary magnesium (Mg) intake and magnesium depletion score (MDS) among American adults with osteoporosis.MethodsThe continuous data from the National Health and Nutrition Examination Survey 2005–2006, 2007–2008, 2009–2010, 2013–2014, and 2017–2018 were merged to ensure a large and representative sample and a total of 14,566 participants were enrolled for the analysis. The weighted multivariate linear regression model was performed to assess the lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The results of the meta-analysis demonstrated significantly reduced serum Mg levels in osteoporotic postmenopausal women [ 33 ], although this association was country-specific, being significant in European but not Asian populations [ 34 ]. In addition, a recent systematic review and meta-analysis showed a significant positive relationship between dietary Mg intake and hip BMD values in older adults [ 35 ], corroborating the observed negative association between Mg intake and osteoporosis [ 36 ]. The results from a large prospective study demonstrated that higher dietary Mg intake is associated with a reduced risk of future osteoporotic fractures in American adults [ 37 ].…”
Section: Magnesium (Mg)mentioning
confidence: 66%
“…The results of the meta-analysis demonstrated significantly reduced serum Mg levels in osteoporotic postmenopausal women [ 33 ], although this association was country-specific, being significant in European but not Asian populations [ 34 ]. In addition, a recent systematic review and meta-analysis showed a significant positive relationship between dietary Mg intake and hip BMD values in older adults [ 35 ], corroborating the observed negative association between Mg intake and osteoporosis [ 36 ]. The results from a large prospective study demonstrated that higher dietary Mg intake is associated with a reduced risk of future osteoporotic fractures in American adults [ 37 ].…”
Section: Magnesium (Mg)mentioning
confidence: 66%
“…In particular, as a collateral finding to our main results, one large study found statistically significantly lower (263.1 ± 114.3 mg/day) magnesium intake in subjects with osteoporosis (N = 14,566 subjects with osteoporosis; 82.2% were females) compared with subjects without osteoporosis (304.5 ± 126.5 mg/day, p < 0.001). The same study also found an increased risk of osteoporosis associated with a magnesium depletion score higher than 3 [odds ratio of 1.785 (95% CI between 1.544 and 2.064), p < 0.001] [ 125 ]. Another cohort published in 20202 on 194 young females showed that women with insufficient magnesium intake had lower bone mineral density ( p = 0.03) [ 126 ].…”
Section: Discussionmentioning
confidence: 95%
“…The threshold values of osteoporosis have been described elsewhere. They were 0.68, 0.59, 0.49, and 0.78 g/cm2 for the total femur, femur neck, trochanter, and intertrochanter, respectively [ 31 ]. The diagnosis of diabetes was based on any of the following criteria were met: (1) A self-reported diagnosis of diabetes.…”
Section: Methodsmentioning
confidence: 99%